PENANDA ASPEK SECARA MORFOLOGIS DALAM BAHASA INDONESIA - I Nengah Mileh (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
The Indonesian language has particle category used to explain the meaning of aspectual verbal. The aspectual particle can support various aspects, such as (a) perspective, that is the aspect referring to an overview of events as a whole (complete situation), and (b) Imperfective, namely aspects that describe imperfect events (incomplete situations). This study aims to find markers of morphological aspects that determine the types of aspects in Indonesian. Observation methods and note taking techniques were used in data collection, synchronic descriptive methods were used to analyze data assisted by inductive or deductive techniques, while the presentation of analysis results used informal methods, namely methods of presenting the results of the analysis using the formulation of words. In this study, ten types of aspects were found, namely durative, frequentative, inkoative, perfective, futurative, iterative, habituative, momentant, spontaneity, and indeterminative aspects. Morphological aspect markers that determine the appearance of the types of aspects in Indonesian are affixation (affixation), repetition (reduplication), and compounding. Keywords: aspect, language, morphology